INCREASE SERVICE SALES TURNOVER THROUGH A DIGITAL MARKETING APPROACH: EFFECTIVE? - Nuryadi; Pratama, Devangga Putra Adhitya; Arifin, Syamsul (Sekolah tinggi ilmu ekonomi pemuda, 2024)
The difference in turnover fluctuations with a tendency to decline in the last few sales periods is the basis for research in analyzing the effectiveness of the digital marketing approach. The role of digital marketing in increasing sales turnover of service products at PT Fokus Kualitas Utama places a new strategic decision when it is declared effective. The data studied in the form of observations of digital marketing platforms, and interview results from sources about the role of digital marketing to increase turnover of service companies. The results of this study are based on observations of data on the use of digital marketing and use quantitative research methods that are collaborated with data validation of findings in the field from interviews and observation of documentation. The use of the t-test or paired-sample test in this study is intended as an effort for researchers to determine the level of change in turnover from the results of comparing the use of digital marketing approaches with conventional approaches with data sources from the same subject. The results of this study conclude that the roles and benefits obtained when using digital marketing effectively make it easier to expand interactions which are an opportunity to increase service sales turnover at PT Fokus Kualitas Utama.